Quiet and Disturbed Time Characteristics of Blanketing Es (Esb) During Solar Cycle 23 - Yadav, Virendra; Kakad, Bharati; Bhattacharyya, A.; Pant, T.K. (My University, 2017)
A sporadic E layer with dense ionization blocks the upper ionospheric layers in ionosonde observations and it is called, blanketing sporadic E (Esb). Although earlier studies have demonstrated that Esb occurrence is dependent on solar activity, seasons, local time, and equatorial electrojet/counter equatorial electrojet (EEJ/CEEJ) strength, the physics behind this dependence is not well established particularly at the dip equatorial stations. Moreover, fewer comprehensive studies are available on Esb. Present work is a detailed statistical study of Esb occurrence and its characteristics during solar cycle 23 (1996–2006) at Indian dip equatorial station Trivandrum (dip latitude 0.5∘N). In present study, solar flux dependence of Esb occurrence is clearly evident not only for magnetically quiet but also for the disturbed periods with maximum during low solar activity. Known seasonal peak Esb occurrence during summer (May–August) is found to be dominated by larger percentage of total blanketing events (fbEs ≥ 8 MHz) on magnetically disturbed days as compared to quiet days. We noticed prevalent Esb occurrence in the postmidnight (00–06 India Standard Time) periods during low solar activity. Besides Esb characteristics, the present study aims to investigate effect of solar flux on association of Esb and CEEJ. Coexistence of Esb and CEEJ is emphasized in earlier observational studies. However, any dependence of their association on solar flux is not yet examined. We find that their association is weaker during low solar activity as compared to high solar activity in summer, indicating that Esb occurrence is highly likely on CEEJ days during high solar activity periods.
Keywords: Solar cycle 23; Sporadic E; Esb; Blanketing Es; Blanketing Es; Blanketing sporadic E